Clinical risk management – a 3‐year experience of team timeout in 18 081 ophthalmic patients. Issue 2 (16th July 2016) - Weingessel, Birgit; Haas, Michaela; Vécsei, Christina; Vécsei‐Marlovits, Pia Veronika
Abstract: Purpose: Clinical risk management aims to identify, analyse and avoid errors and risks systematically to improve patient's safety. Preoperative checklists to prevent mistakes have gained importance in the last few years. A so‐called team timeout checklist was introduced in October 2011 at the Department of Ophthalmology, Hietzing Hospital, Vienna. The purpose of the study is to evaluate the benefits and demonstrate the value of team timeout. Methods: After the team timeout had been in use for 6 months, all near misses that occurred over a period of 34 months were assigned to the following groups: wrong side, wrong lens, wrong patient and miscellaneous. Results: Eighteen thousand and eighty‐one surgeries were performed in the specified period; 53 cases of 'wrong side' and 52 cases of 'wrong intraocular lens' were noted. Ninety‐six near misses concerned the patients' data and 38 concerned documentation. A reduction of near misses was noted after an adaptation phase of 3 months. Conclusions: Team timeout proved valuable, as it improved the patients' safety with minimum effort. Errors may occur despite several preoperative controls and can be detected by performing team timeout.